The sternalis muscle in cadavers: Anatomical facts and clinical significance - N.A. Rahman; S. Das; I. Maatoq Sulaiman; K.P.P. Hlaing; F. Haji Suhaimi; A.A. Latiff; F. Othman (Societ' Editrice Universo, 2024)
The sternalis is an anomalous muscle located in the anterior wall of thorax and several past reports have described its presence with clinical implications. The sternalis muscle may be incidentally detected during routine cadaveric dissections and autopsies. We observed the presence of anomalous sternalis muscle on both sides of the anterior chest wall in 25 cadavers (n = 50), over a span of three years. Out of a 50 cases, we observed a single case of sternalis on the right side of the 55-year-old male cadaver (2%). The sternalis was found to be absent in the rest 49 cases (98%). The sternalis muscle displayed an oblique course in the anterior wall of the thorax. The muscle originated near the seventh costal cartilage extending obliquely upwards to insert into the second costal cartilage close to the sternum. The originating portion of the muscle was located at a distance of 3.5 cm lateral to the mid-sternal plane. The vertical length and the maximum width of the anomalous sternalis muscle measured 9 cm and 1.9 cm, respectively. The fibers of the muscle vertically ascended upwards. No other associated anomalies were observed in the same cadaver. The presence of sternalis muscle is considered to be a rare variation with no earlier studies being performed in the Malaysian population. The anomalous sternalis muscle may be important for reconstructive surgeons performing mastectomy and radiologists interpreting mammograms. Thus, the sternalis muscle may be academically, anthropologically and surgically important.